(untitled) (Revista cientifica In Vestigium Ire, 2016)
This study constitutes a correlative descriptive research that aims to determine the correlation between investment in malls and generated employment in the city of Arequipa, for which an econometric model was developed which is determined by an equation linear, which considers variables Investment, Employment, Unemployment, Gross Domestic Product, Consumer Price Index and Basic Salary; The results show that there is a high degree of correlation between the variables of investment and 21 unemployment, lower unemployment in- creased investment. In addition, a survey questionnaire aimed at workers malls to describe your employment situation is developing.